ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP KINERJA PERBANKAN DI INDONESIA - WIDODO, CLARA HADI (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to knows the effect of macroeconomic condition which proxied from five macroeconomic variabels (inflation, interest rate, indeks composite (IHSG), gross domestic bruto (GDP) and exchange rate) on bank’s performance (return on aset (ROA) dan capital adequacy ratio (CAR)). The data are obtained from Statistik Perbankan Indonesia (SPI) during the period of 2009-2015 as informed by official websites of OJK, BI and macroeconomic data by websites BPS. The analyz method that used in this research is Partial Least Square (PLS) with SmartPLS 3 aplication program. The study reveals that inflation and kurs contribute dominately to macroeconomics condition, while banks performance dominated by contribution of capital adequacy ratio (CAR). The effect of macroeconomic condition on banks performance significantly proved, whith only two macroeconomic variabel inflation and kurs have significantly influences on banks performance. Keywords: bank’s performance, macroeconomic variabel, partial least square (PLS)